Expression of insulin, glucagon, somatostatin, and pancreatic polypeptide in the pancreas of the eurasian moorhen (Gallinula chloropus) - Abdellatif, Ahmed M. (Slovenian veterinary research, 2023)
The pancreas is a complex gland that possesses both endocrine and exo-crine functions. The present study investigated the gross anatomy, histochemical fea-tures, and immunohistochemical expression of insulin, glucagon, somatostatin, and pancreatic polypeptide in the pancreas of the Eurasian moorhen. Grossly, the pancreas consisted of three duodenal lobes and unpaired splenic and gastric lobes. The pancre-atic capsule appeared thin with no distinct lobulation pattern. Three islet types were observed namely alpha, beta, and mixed types. The alpha-type islets formed mainly of glucagon- and somatostatin-expressing cells. The beta-type islets appeared relatively smaller than the two other islet types and formed predominately of insulin-expressing cells with a limited number of other endocrine cells. The mixed islets were formed by almost equal proportions of insulin-, glucagon- and somatostatin-expressing cells. A higher number of alpha-type islets was observed in the splenic lobe than in other pan-creatic lobes. Unlike other pancreatic endocrine cells which appeared oval or triangular in shape, somatostatin-expressing cells appeared with irregular outlines with cytoplas-mic processes contacting each other’s forming a meshwork within the islet. The results of this study revealed species-specific features of the endocrine and exocrine pancreas in the Eurasian moorhen and could suggest pancreatic functional differences depend-ing on feeding habits.
Keywords: agresija; deslorelinski implantat; dolgo delujoči GnRH; Glucagon; Insulin; Pankreas; psica; Somatostatin; spolno vedenje